Fenomena Lingkaran Setan Mega Korupsi Menjelang Pemilihan Umum di Indonesia: Dampaknya terhadap Kualitas Layanan dan Regulasi Pemerintahan Terpilih - Sidiq, Mohammad Ali Nur; Wahyuni, Mutia (Bestuurskunde: Journal of Governmental Studies, 2024)
Corruption cases in Indonesia typically peak in the year leading up to general elections, often accompanied by the emergence of the National Mega Corruption phenomenon. The high logistics costs of general elections have historically fueled corruption. This study analyzes corruption, including mega corruption, following Indonesia's adoption of an open election system and assesses the impact of corruption on government service quality and regulations. Research methods include Exploratory Data Analysis, Vector Error Correction Model (VECM), and Comparative Ordinary Least Square. Findings show that (1) Democracy in Indonesia is closely linked to corruption and mega corruption at both central (executive and legislative) and regional (regional head election) levels; (2) Corruption and mega corruption trends preceding general elections are expected to persist in the 2024 and 2029 elections; (3) Political corruption leads to poor government service quality and regulation; (4) The shock of pre-election corruption will affect government quality for over two decades. This research emphasizes the need for electoral process and corruption enforcement reforms in Indonesia. Unmitigated, pre-election corruption can lead to poor governance and reduced public welfare.